School Climate and Students Dropouts: A Global Perspective - Yusof, Najeemah Mohd (ASPENSI, 2012)
ABSTRACT: A number of scholars have identified considerable features in describing and conceptualizing school climate, using the characteristics of the school total means of operation. This paper discusses on school climate and students dropouts, focussing on a global perspective. This reviews the conceptual position of students dropouts from the perspective of the developed and developing nations, various school climate factors that lead to students dropouts where outlined, and the features of positive and negative school climate where clarified. Both in the developed and developing nations, it was identified that school climate can force students to dropouts from school and at the same time help a students to be successful. But the school climate of the developing nations is facing challenges of schools facilities to build up a fruitful teaching and learning climate. Some major problems facing schools of the developed nations are not the issues of policy toward school, because the schools have all the facilities required for a good school climate.KEY WORD: School climate, studentsâ dropout, developed and developing nations, and global perspective.IKHTISAR: Beberapa sarjana telah mengenal pasti ciri-ciri yang besar dalam menerangkan dan menkonsepkan iklim sekolah, menggunakan ciri-ciri bagaimana sesebuah sekolah beroperasi. Kertas kerja ini membincangkan tentang iklim sekolah dan keciciran pelajar yang memberi tumpuan kepada perspektif global. Kertas ini mengkaji kedudukan konsep pelajar tercicir dari perspektif negara-negara maju dan membangun, pelbagai faktor iklim sekolah yang membawa kepada keciciran pelajar dikenalpasti, dan ciri-ciri iklim sekolah yang positif dan negatif dijelaskan. Di negara-negara maju dan membangun telah dikenal pasti bahawa iklim sekolah boleh menyebabkan pelajar tercicir dari sekolah dan pada masa yang sama membantu pelajar untuk berjaya. Tetapi iklim sekolah di negara-negara membangun menghadapi cabaran bagi menyediakan kemudahan sekolah untuk membina dan menghasilkan pengajaran dan pembelajaran yang terbaik. Beberapa masalah utama yang dihadapi oleh sekolah-sekolah di negara-negara maju bukanlah berkaitan dengan isu-isu dasar kerana kesemua sekolah di negara maju mempunyai kemudahan yang diperlukan untuk mempamerkan iklim sekolah yang baik.KATA KUNCI: Iklim sekolah, keciciran perlajar, negara maju dan membangun, serta perspektif global.About the Author: Dr. Najeemah Mohd Yusof is a Senior Lecturer at the School of Educational Studies USM (Science University of Malaysia), USM Campus, 11800 Minden, Pulau Pinang, Malaysia. She can be reached at: najineen@usm.myHow to cite this article? Yusof, Najeemah Mohd. (2012). âSchool Climate and Students Dropouts: A Global Perspectiveâ in ATIKAN: Jurnal Kajian Pendidikan, Vol.2(2) Desember, pp.175-194. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung and FKIP UNSUR in Cianjur, West Java, ISSN 2088-1290. Chronicle of the article: Accepted (October 5, 2012); Revised (November 10, 2012); and Published (December 15, 2012).